Effects of Hf4+ substitute on the enhanced electrostrain properties of 0.7BiFeO3-0.3BaTiO3-based lead-free piezoelectric ceramics. Issue 8 (15th April 2022) - Zeng, Fangfang; Zhou, Chuang; Zhang, Chao; Jiang, Lei; Zhang, Jianjia; Guo, Huitao; Chen, Yuxin; Lu, Wenzhong; Cai, Wei; Zhang, Guangzu; Hu, Yongming; Fan, Guifen
Abstract: The 0.7Bi1.05 FeO3 -0.3BaHf x Ti(1− x ) O3 (BF-BHT- x ) ceramics are prepared by using conventional method. The mechanism of large electric-induced strain is studied in detail through Rietveld refinement, transmission electron microscopy (TEM), and piezoelectric force microscopy (PFM). The BF-BHT-0.05 ceramics, which possess the coexistence of cubic ( Pm -3 m ) and rhombohedral ( R 3 c ) phase proved by Rietveld refinement and TEM measurement, have the maximum electric-induced strain of S max = 0.58% at 130 kV/cm (1 Hz). The reduced potential barrier is beneficial to the switching and reorientation of domain under an external electric field due to the coexistence of cubic and rhombohedral phase. A mass of nanodomains embedded into the microdomains, which is conducive to domain switching, are observed obviously through PFM. Therefore, the findings show that the large strain is because the external electric field drives the conversion mixed phase into the major rhombohedral phase, the reduced potential barrier, and the nanodomain in macrodomain.